Shear-solvo defect annihilation of diblock copolymer thin films over a large area - Kim, Ye Chan; Shin, Tae Joo; Hur, Su-Mi; Kwon, Seok Joon; Kim, So Youn (AMER ASSOC ADVANCEMENT SCIENCE, 2019)
Achieving defect-free block copolymer (BCP) nanopatterns with a long-ranged orientation over a large area remains a persistent challenge, impeding the successful and widespread application of BCP self-assembly. Here, we demonstrate a new experimental strategy for defect annihilation while conserving structural order and enhancing uniformity of nanopatterns. Sequential shear alignment and solvent vapor annealing generate perfectly aligned nanopatterns with a low defect density over centimeter-scale areas, outperforming previous single or sequential combinations of annealing. The enhanced order quality and pattern uniformity were characterized in unprecedented detail via scattering analysis and incorporating new mathematical indices using elaborate image processing algorithms. In addition, using an advanced sampling method combined with a coarse-grained molecular simulation, we found that domain swelling is the driving force for enhanced defect annihilation. The superior quality of large-scale nanopatterns was further confirmed with diffraction and optical properties after metallized patterns, suggesting strong potential for application in optoelectrical devices.
Keywords: BLOCK-COPOLYMERS; ORIENTATION; ALIGNMENT; PATTERN; ARRAYS; ORDER